P860 The Costs of Inflammatory Bowel Diseases in High-Income Settings. (30th January 2023) - Burisch, J; Zhao, M; Odes, S; De Cruz, P; Vermeire, S; Bernstein, C N; Kaplan, G G; Duricova, D; Greenberg, D; Melberg, H O; Watanabe, M; Ahn, H S; et al.
Abstract: Background: Crohn's disease (CD) and ulcerative colitis (UC), together known as inflammatory bowel diseases (IBD), affect approximately seven million people globally. The continuous rise in IBD prevalence and the aging of populations will inevitably lead to an increasing use of health care resources. In parallel with these trends, continuing innovations in IBD therapeutics, diagnostics, and preventatives are creating more options for IBD patients seeking to reduce their disease burden. These trends pose an imminent burden on health care systems and require that we identify modifiable cost drivers in IBD care and develop strategies for delivering equitable and affordable care for all patients. Methods: This Lancet Gastroenterology & Hepatology Commission, consisting of a diverse faculty of health care professionals with expertise in the field of IBD and health economists, was formed to deliver an extensive summary of the literature and discuss key topics on the costs and cost-effectiveness of treating IBD in the present, and how this is likely to look in the future. Furthermore, it offers suggestions for how to deliver affordable IBD care in the coming years. The report's focus was on high-income countries in Europe, North America, Australia and New Zealand, and Asia. Results: The Commission drew together a wide range of expertise to discuss the current costs of IBD care, the drivers of increasing costs, as well as how to deliver affordable care for IBD in the future. The key conclusions are that (i) increases in health care costs must be evaluated against improved disease control and reductions in indirect costs, and (ii) that overarching systems for data interoperability, registries, and big data approaches must be established for continuous assessment of effectiveness, costs, and cost-effectiveness of care. International collaborations should be sought in order to evaluate novel models of care (such as value-based health care, including integrated health care and participatory health care models), as well as to improve the education and training of clinicians, patients, and policymakers. Measures to reduce the costs of IBD care are summarised in Table 1. Conclusion: Increases in health care costs must be evaluated against improved disease control and reductions in indirect costs. Evaluations should be systematically aligned between countries and regions. Detailed analysis of the current epidemiology and the likely effects of changing IBD management on disease course and socioeconomic outcomes is essential; and will become even more imperative in the era of precision medicine, where complex biotechnologies will require expensive analyses, highly skilled personnel, and drug development for what may sometimes be relatively small patient groups.